Optimizing the Competitiveness of Ledre Khas Bojonegoro UMKM Through Sharia Management Principles - Retno Khabibatuni’mah; Abdur Rohman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Ledre UMKM typical of Bojonegoro is part of the local culinary heritage that has high economic and cultural value. However, in facing increasingly competitive market competition, a strategy is needed to strengthen competitiveness that is not only based on economy, but also value. This study aims to analyze the potential for implementing sharia management principles in optimizing the competitiveness of Ledre UMKM in the traditional food sector. This study examines various scientific sources related to UMKM, competitiveness strategies, and sharia management principles such as amanah, adl (justice), syura (deliberation), and ihsan (quality and sincerity of work). The results of the study indicate that the application of these principles can improve business governance, strengthen trust relationships with consumers, and create sustainable and ethical added value. This approach is considered relevant to developing local UMKM that are economically superior and based on Islamic values.